Study of Eco-Innovation and its Implications for Batik MSME Business Performance in Giriloyo Village, Yogyakarta - Nuryanti Sastradinata, B Lena; Rahma Daniati, Ranti (JURNAL EKBIS, 2023)
This research aims to investigate the influence of eco-innovation on the business performance of Batik MSMEs in Giriloyo Village, Yogyakarta. Eco-innovation refers to business practices that focus on environmentally friendly product and process innovation. The issues of global warming, climate change, pollution and waste problems not only pose threats to human life, but also have an impact on business activities. In an era of increasingly intense economic competition, entrepreneurs are required to improve their business performance. According to experts, entrepreneurship as part of the ecological system has an important role in overcoming environmental problems through sustainable transformation of products and processes. The contribution of environmentally friendly products and processes provides not only economic value, but also significant environmental benefits. This encourages entrepreneurs to improve their innovation capabilities in facing social and environmental challenges. In this context, this research aims to improve the business performance of Batik MSMEs in Giriloyo Village, Yogyakarta. The survey was conducted on 36 Batik MSMEs in Giriloyo Village as the research population. By using simple linear regression analysis, the research results show that eco innovation has a positive and significant effect on the business performance of Batik MSMEs. The level of eco innovation in Batik MSMEs in Giriloyo Village is relatively good Based on the results of this research, it can be concluded that the higher the level of eco innovation implemented, the higher the business performance of Batik MSMEs in Giriloyo Village. The implication is that entrepreneurs need to consider eco innovation as an important strategy in improving their business performance. Steps to implement eco innovation, such as developing environmentally friendly products and sustainable production processes, can provide long-term economic benefits and also maintain environmental sustainability. To optimize the results of this research, it is recommended that Batik MSME entrepreneurs in Giriloyo Village continue to increase awareness of its importance. eco innovation and implement it actively. The government can also provide support in the form of policies and incentives to encourage entrepreneurs to implement sustainable business practices. In this way, Batik MSMEs in Giriloyo Village can gain a sustainable competitive advantage and contribute to environmentally friendly economic development.